Advancements in the Treatment of Urinary Stress Incontinence: Current Strategies and Future Directions - Lenard, Paweł; Makuch, Rafał; Chrościcka, Alicja; Gała, Kamil; Czajka, Andrzej; Kucharski, Adam; Michalska, Sara; Pilarski, Konrad; Dewicka, Martyna; Wawrzyniak, Alicja Maria (Quality in Sport, 2024)
Introduction and purpose Stress urinary incontinence remains a prevalent issue affecting both women and men, significantly impacting their quality of life and social participation. Stress urinary incontinence (SUI) is defined as the sudden, involuntary loss of urine secondary to increased intraabdominal pressure, which has a negative impact on the patient’s quality of life. SUI may be precipitated by a number of activities, including coughing, laughing, sneezing, straining, or exercising. Modern diagnostic and therapeutic approaches have improved outcomes for those affected, yet challenges persist, including accurate diagnosis and understanding of the underlying pathophysiology, as well as the development of effective treatment algorithms. The aim of the article was to present current guidelines for treatment of stress urinary incontinence depending on the individual patient’s requirements. Material and methods Review and summary of research studies available in open source format on Google Scholar and PubMed. The literature was reviewed using the keywords.